Carta del Capitán C. H. Watts - Todd, Roberto H.; Watts, C. H. (My University, 1899)
Carta del Capitán C. H. Watts en relación a la inspección de armas.
Keywords: Watts, C. H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Watts, C. H.--Correspondence.; Todd, Roberto H.--Correspondencia.